Flare of Antiphospholipid Syndrome in the Course of COVID-19 - Maria, Alexandre Thibault Jacques; Diaz-Cau, Isabelle; Benejean, Jean-Marc; Nutz, Anaïs; Schiffmann, Aurélie; Biron-Andreani, Christine; Guilpain, Philippe (TH Open, 2020)
We report the case of a 48-year-old man followed since 2013 for primary antiphospholipid syndrome (APLS) revealed by venous thromboembolism in the presence of antiphospholipid antibodies (APL-Abs, anticardiolipin and anti-β-2-glycoprotein-1), who decompensated in the course of coronavirus disease (COVID-19). Despite efficient anticoagulation, he suffered bilateral adrenal glands hemorrhage and limb arterial ischemia. The tropism of severe acute respiratory syndrome coronavirus-2 for endothelium can lead to microangiopathy and increased risk for thrombosis. If APL-Abs positivity can be an epiphenomenon under inflammatory and prothrombotic conditions, COVID-19 was herein responsible for disseminated thrombosis and a threat of catastrophic APLS, despite efficient anticoagulation.
Keywords: COVID-19; infection; thrombosis; antiphospholipid syndrome; hydroxychloroquine